Integrated metabolomic and transcriptomic analyses revealed metabolite variations and regulatory networks in Cinnamomum cassia Presl from four growth years - Gao, Hongyang; Shi, Min; Zhang, Huiju; Shang, Hongli; Yang, Quan (Frontiers in Plant Science, 2024)
To understand the mechanism of the dynamic accumulation of active ingredients in Cinnamomum cassia Presl, metabolomic and transcriptomic analyses of 5 8 years old C. cassia were performed. A total of 72 phenylpropanoids, 146 flavonoids, and 130 terpenoids showed marked changes. Most phenylpropanoids and flavonoids showed markedly higher abundances in 6-year-old C. cassia than in others, which was related to the higher expression of genes that synthesize and regulate phenylpropanoids and flavonoid. We identified transcription factors (TFs) and genes involved in phenylpropanoids and flavonoids synthesis and regulation through co-expression network analyses. Furthermore, most of the terpenoids in 5-year-old C. cassia showed markedly higher abundances than in others, which was due to the differentially expressed genes upstream of the terpenoids pathway. The results of our study provide new insights into the synthesis and accumulation of phenylpropanoid, flavonoids and terpenoids in C. cassia at four growth stages.